Evaluation and Pharmacological Screening of Endophytic fractions of Centella asiatica Linn Leaves for In-vitro Antioxidant Activity - R. A. Shastry; P. V. Habbu; D. M. Smita; Sudhir. R. Iliger; V. H. Kulkarni (Current Aspects in Pharmaceutical Research and Development Vol. 6, 2021)
In this study, we isolated fungal endophytes from Centella asiatica Linn leaves, followed by fermentation and extraction of fungal endophytes with non-polar solvents like chloroform, ethyl acetate, and n-butanol. Preliminary phytochemical analysis of endophytic crude extracts of leaves was also performed to detect the presence of primary and secondary metabolites, which was followed by an invitro free radical scavenging activity assay using reducing power, DPPH, and hydroxyl radical assays.To isolate a possible secondary metabolite, the chloroform fungal endophytic fractions were submitted to column chromatography using a gradient elution approach. With increasing concentrations, the reducing power of endophytic extracts of C. asiatica Leaf (CAL-1) (50-450\(μ\)g/ml) increased. Reaction with DPPH radicals of CAL-1 showed good scavenging activity. The IC50 values for Ascorbic acid, chloroform fraction, ethyl acetate and n- butanol fraction were found to be 30.33 \(μ\)g /ml, 66.58 \(μ\)g/ml, 79.33 \(μ\)g /ml and 96.39 \(μ\)g/ml respectively. The IC50 values for mannitol, chloroform fraction, ethyl acetate, and n-butanol fraction were found to be121.06 \(μ\)g / ml, 141.21 \(μ\)g/ml, 181.80 µg/ml and 189.90 \(μ\)g/ml respectively, in the hydroxyl radical assay. Endophytic crude fractions of ethyl acetate had significantly higher antioxidant activity than other fractions. As a result, ethyl acetate fungal endophytic fractions of Centella asiatica Linn leaves have the potential to be used as an antioxidant in the prevention of oxidative stress caused by free radicals. Further investigations are needed to isolate and characterize the potential polyphenolic compounds which are present in the endophytic extracts including their mode of action in the management of oxidative stress caused by the free radicals.